Mica-metal oxide-based composite nano material and preparation method and application thereof
By using mica-metal oxide composite nanomaterials as catalysts, the existing catalysts have been solved, the problems of single activity, high price and insufficient durability are achieved, and catalytic effects with high activity, stability and low cost are achieved. They are suitable for applications such as electrolytic hydrogen production.
Patent Information
- Application Number
- CN202510084160.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2045-01-20
AI Technical Summary
The catalysts in the existing electrochemical oxygen reduction reaction, oxygen evolution reaction and hydrogen evolution reaction have problems such as single catalytic activity, expensive price and insufficient durability, and transition metals and their compounds cannot meet application needs without regulation.
Mica-metal oxide composite nanomaterials are used as catalysts, where mica powder is used as a support to support nickel oxide nanosheets, and are prepared by ball milling and calcining to form composite nanomaterials with high activity and stability.
It improves the activity and stability of the catalyst, reduces the amount of transition metal nickel, simplifies the preparation process, reduces costs, and is easy to promote in industrialization.
Smart Images

Figure CN119900043A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of hydrogen production by electrolysis of water, and in particular to a mica-metal oxide composite nanomaterial and a preparation method and application thereof. Background Art
[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.
[0003] Hydrogen is recognized as an important carrier for promoting sustainable energy transformation due to its high energy density and zero carbon emission characteristics. It is the most promising clean energy in the 21st century. Hydrogen production by water electrolysis has become an important technology in the field of hydrogen production due to its advantages such as simple operation and pure products. However, the slow kinetics and large overpotential problems in the electrochemical oxygen reduction reaction (ORR), oxygen evolution reaction (OER) and hydrogen evolution reaction (HER) have largely hindered these reactions from achieving high energy efficiency and output power in various related applications. Therefore, ideal electrocatalysts with high activity, high stability and low economic cost are extremely important for accelerating the redox kinetic reactions of electrochemical processes.
[0004] So far, noble metal catalysts, such as Pt-based, Ru-based, and Ir-based catalysts, are still commercial catalysts for electrochemical oxygen reduction reaction, oxygen evolution reaction, and hydrogen evolution reaction. However, noble metal catalysts are not only expensive and lack long-term durability, but also have a single catalytic activity, which limits their further development.
[0005] In recent years, transition metals and their compounds have been considered as potential substitutes for precious metals due to their abundant reserves, adjustable catalytic properties and low prices. However, the catalytic activity, stability and versatility of unregulated transition metals and their compounds cannot meet application requirements. Summary of the invention
[0006] In order to overcome the above problems, the present invention provides a mica-metal oxide composite nanomaterial and a preparation method and application thereof.
[0007] In order to achieve the above technical objectives, the present invention adopts the following technical solutions: The first aspect of the present invention provides a mica-metal oxide composite nanomaterial, which uses mica powder as a carrier and is loaded with nickel oxide nanoparticles.
[0008] Among them, the particle size of mica powder is 5~8 μm.
[0009] The nickel oxide nanoparticles are nanosheets, and the particle size of the nickel oxide nanosheets is 1-2 μm.
[0010] The second aspect of the present invention provides a method for preparing the mica-metal oxide composite nanomaterial according to the first aspect, comprising the following steps: (1) ball-milling mica powder and nickel powder to obtain a precursor; (2) calcining the precursor in an oxygen atmosphere to obtain the mica-metal oxide composite nanomaterial.
[0011] The third aspect of the present invention provides the use of the mica-metal oxide composite nanomaterial described in the first aspect as a catalyst.
[0012] A fourth aspect of the present invention provides a catalyst layer slurry for producing hydrogen by electrolysis of water, comprising a binder, a conductive material and the mica-metal oxide composite nanomaterial described in the first aspect.
[0013] The beneficial effects of the present invention are: (1) The present invention provides a mica-metal oxide composite nanomaterial and its preparation method and application. The composite nanomaterial uses mica powder as a carrier and is loaded with nickel oxide nanoparticles. Using mica powder as a carrier of nickel oxide nanoparticles can not only solve the problem of reduced catalytic effect of nickel oxide nanoparticles due to agglomeration, but also improve the overall catalytic life of the composite nanomaterial due to its good wear resistance.
[0014] (2) In the present invention, mica powder is used as a carrier of nickel oxide nanoparticles, which can improve the catalytic effect while reducing the amount of transition metal nickel.
[0015] (3) The mica-metal oxide composite nanomaterial provided by the present invention has a simple preparation method, low cost, and is easy to promote industrialization. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.
[0017] Figure 1 a~d are scanning electron microscope images of mica-metal oxide composite nanomaterial NiO / Mica at different magnifications; Figure 2 XRD images of mica powder, precursor Ni / Mica, and mica-metal oxide composite nanomaterial NiO / Mica; Figure 3 This is the EDX image of mica-metal oxide composite nanomaterial NiO / Mica; Figure 4OER polarization curves of nickel-iron foam substrate, mica powder, precursor Ni / Mica, mica-metal oxide composite nanomaterial NiO / Mica and RuO2; Figure 5 The Tafel slopes of the OER polarization curves of nickel-iron foam substrate, mica powder, precursor Ni / Mica, mica-metal oxide composite nanomaterial NiO / Mica, and RuO2; Figure 6 The electrochemical impedance test results of nickel-iron foam substrate, mica powder, precursor Ni / Mica, mica-metal oxide composite nanomaterial NiO / Mica and RuO2 are shown; Figure 7 The stability test results of mica-metal oxide composite nanomaterial NiO / Mica; Figure 8 Polarization curves of the working electrode and substrate prepared from NiO / Mica composite nanomaterials with different Ni contents. DETAILED DESCRIPTION
[0018] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.
[0019] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit exemplary embodiments according to the present invention. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprising" and / or "including" are used in this specification, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.
[0020] A first typical embodiment of the present invention provides a mica-metal oxide composite nanomaterial, which uses mica powder as a carrier and is loaded with nickel oxide nanoparticles.
[0021] Among them, the particle size of mica powder is 5~8 μm.
[0022] The nickel oxide nanoparticles are nanosheets, and the particle size of the nickel oxide nanosheets is 1-2 μm.
[0023] A second typical embodiment of the present invention provides a method for preparing the mica-metal oxide composite nanomaterial according to the first aspect, comprising the following steps: (1) ball-milling mica powder and nickel powder to obtain a precursor; (2) calcining the precursor in an oxygen atmosphere to obtain the mica-metal oxide composite nanomaterial.
[0024] In one or more embodiments, in step (1), the mass ratio of the mica powder to the nickel powder is 3:2-6, preferably 3:5.
[0025] In one or more embodiments, in step (1), a ball milling aid needs to be added during the ball milling process, and the ball milling aid is ethanol.
[0026] In one or more embodiments, in step (1), during the ball milling process, the ball-to-material ratio is (24-26): (1.8-2.2), preferably 25:2.
[0027] In one or more embodiments, in step (1), during the ball milling process, the rotation speed of the ball mill is 350-500 r / min, preferably 400 r / min; and the ball milling time is 7-9 h, preferably 8 h.
[0028] In one or more embodiments, in step (2), during the calcination process, the calcination temperature is 550-700°C, preferably 600°C; and the calcination time is 7-9 h, preferably 8 h.
[0029] Preferably, during the calcination process, the heating rate is 8-12°C / min, preferably 10°C / min.
[0030] A third typical embodiment of the present invention provides the use of the mica-metal oxide composite nanomaterial described in the first aspect as a catalyst.
[0031] In one or more embodiments, the application includes: producing hydrogen by electrolyzing water.
[0032] A fourth typical embodiment of the present invention provides a catalyst layer slurry for producing hydrogen by electrolysis of water, comprising a binder, a conductive material and the mica-metal oxide composite nanomaterial described in the first aspect.
[0033] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in conjunction with specific embodiments.
[0034] Example 1 Preparation of mica-metal oxide composite nanomaterials: (1) Pretreatment of mica powder: Place the mica powder in a pulverizer for pulverization; add anhydrous ethanol to the pulverized mica powder and let it stand for 2 hours. Take the supernatant and centrifuge it (15,000 rpm for 8 minutes). Collect the precipitate and vacuum dry it in a vacuum drying oven at 60°C to obtain mica powder with a nanoparticle size of 5 to 8 μm.
[0035] (2) Add 3 g of mica powder obtained in step (1) and 5 g of nickel powder into a ball mill, add 20 mL of ethanol as a grinding aid, add zirconia grinding balls with diameters of 5 mm, 8 mm, and 10 mm, respectively, and a ball-to-material ratio of 25:2, and perform ball milling. The forward rotation time is 30 min, the reverse rotation time is 30 min, the total ball milling time is 8 h, and the rotation speed is 400 r / min.
[0036] The ball-milled sample was placed in a vacuum drying oven and dried at 80 °C for 4 h to obtain a precursor named Ni / Mica.
[0037] (3) The precursor Ni / Mica obtained in step (2) was ground into powder using a mortar, and then 200 mg of the sample was weighed and evenly spread on a quartz boat. The sample was heated to 600 °C at a heating rate of 10 °C / min in an air atmosphere using a tube furnace and calcined for 8 h to obtain a mica-metal oxide composite nanomaterial named NiO / Mica.
[0038] Figure 1 This is a scanning electron microscope image of mica-metal oxide composite nanomaterial NiO / Mica. Figure 1 It can be seen that the NiO nanosheets are evenly distributed on the mica powder, which avoids the agglomeration of nickel oxide nanoparticles and exposes more active sites, thereby improving the electrocatalytic performance.
[0039] Figure 2 XRD images of mica powder, precursor Ni / Mica and mica-metal oxide composite nanomaterial NiO / Mica. Figure 2 It can be seen that Mica has a high degree of crystallinity. Three characteristic peaks of Mica can be clearly observed at 2θ=17.8°, 26.8°, and 45.6°, corresponding to the (004), (006), and (224) crystal planes of Mica (26-0911). Two peaks were observed at 2θ=27.2° and 43.3°, which have the characteristics of cubic NiO phase (71-1179). The peaks at 2θ=44.5° and 51.8° are those of Ni (04-0850).
[0040] Figure 3This is the EDX image of mica-metal oxide composite nanomaterial NiO / Mica. Figure 3 It can be seen that the distribution of each element is relatively uniform, and the Ni element can be successfully loaded on mica, thereby ensuring the feasibility of catalysis.
[0041] Example 2 3 g of mica powder obtained in step (1) of Example 1 and 3 g of nickel powder were added to a ball mill, 20 mL of ethanol was added as a grinding aid, and grinding balls made of zirconium oxide were added with diameters of 5 mm, 8 mm, and 10 mm, respectively. The ball-to-material ratio was 25:2. The ball milling was carried out with a forward rotation time of 30 min, a reverse rotation time of 30 min, a total ball milling time of 8 h, and a rotation speed of 400 r / min.
[0042] The ball-milled sample was placed in a vacuum drying oven and dried at 80 °C for 4 h to obtain a precursor named Ni / Mica.
[0043] (3) The precursor Ni / Mica obtained in step (2) was ground into powder using a mortar, and then 200 mg of the sample was weighed and evenly spread on a quartz boat. The sample was heated to 600 °C at a heating rate of 10 °C / min in an air atmosphere using a tube furnace and calcined for 8 h to obtain a mica-metal oxide composite nanomaterial named NiO / Mica.
[0044] Example 3 3 g of mica powder obtained in step (1) of the embodiment and 4 g of nickel powder were added to a ball mill, 20 mL of ethanol was added as a grinding aid, and grinding balls made of zirconium oxide were added with diameters of 5 mm, 8 mm, and 10 mm, respectively. The ball-to-material ratio was 25:2. The ball milling was carried out with a forward rotation time of 30 min, a reverse rotation time of 30 min, a total ball milling time of 8 h, and a rotation speed of 400 r / min.
[0045] The ball-milled sample was placed in a vacuum drying oven and dried at 80 °C for 4 h to obtain a precursor named Ni / Mica.
[0046] The precursor Ni / Mica obtained in step (2) was ground into powder using a mortar, and then 200 mg of the sample was weighed and evenly spread on a quartz boat. It was heated to 600°C at a heating rate of 10°C / min in an air atmosphere using a tube furnace and calcined for 8 h to obtain a mica-metal oxide composite nanomaterial named NiO / Mica.
[0047] Example 4 3 g of mica powder obtained in step (1) of the embodiment and 6 g of nickel powder were added to a ball mill, 20 mL of ethanol was added as a grinding aid, and grinding balls made of zirconium oxide were added, with diameters of 5 mm, 8 mm, and 10 mm, respectively, and a ball-to-material ratio of 25:2. Ball milling was performed, with a forward rotation time of 30 min, a reverse rotation time of 30 min, a total ball milling time of 8 h, and a rotation speed of 400 r / min.
[0048] The ball-milled sample was placed in a vacuum drying oven and dried at 80 °C for 4 h to obtain a precursor named Ni / Mica.
[0049] The precursor Ni / Mica obtained in step (2) was ground into powder using a mortar, and then 200 mg of the sample was weighed and evenly spread on a quartz boat. It was heated to 600°C at a heating rate of 10°C / min in an air atmosphere using a tube furnace and calcined for 8 h to obtain a mica-metal oxide composite nanomaterial named NiO / Mica.
[0050] Example 5 3 g of mica powder obtained in step (1) of the embodiment and 7 g of nickel powder were added to a ball mill, 20 mL of ethanol was added as a grinding aid, and grinding balls made of zirconium oxide were added with diameters of 5 mm, 8 mm, and 10 mm, respectively. The ball-to-material ratio was 25:2. The ball milling process was carried out with a forward rotation time of 30 min, a reverse rotation time of 30 min, a total ball milling time of 8 h, and a rotation speed of 400 r / min.
[0051] The ball-milled sample was placed in a vacuum drying oven and dried at 80 °C for 4 h to obtain a precursor named Ni / Mica.
[0052] The precursor Ni / Mica obtained in step (2) was ground into powder using a mortar, and then 200 mg of the sample was weighed and evenly spread on a quartz boat. It was heated to 600°C at a heating rate of 10°C / min in an air atmosphere using a tube furnace and calcined for 8 h to obtain a mica-metal oxide composite nanomaterial named NiO / Mica.
[0053] Example 6 3 g of mica powder obtained in step (1) of the embodiment and 8 g of nickel powder were added to a ball mill, 20 mL of ethanol was added as a grinding aid, and grinding balls made of zirconium oxide were added, with diameters of 5 mm, 8 mm, and 10 mm, respectively, and a ball-to-material ratio of 25:2. Ball milling was performed, with a forward rotation time of 30 min, a reverse rotation time of 30 min, a total ball milling time of 8 h, and a rotation speed of 400 r / min.
[0054] The ball-milled sample was placed in a vacuum drying oven and dried at 80 °C for 4 h to obtain a precursor named Ni / Mica.
[0055] The precursor Ni / Mica obtained in step (2) was ground into powder using a mortar, and then 200 mg of the sample was weighed and evenly spread on a quartz boat. It was heated to 600°C at a heating rate of 10°C / min in an air atmosphere using a tube furnace and calcined for 8 h to obtain a mica-metal oxide composite nanomaterial named NiO / Mica.
[0056] Example 7 The precursor Ni / Mica obtained in step (2) of Example 1 was ground into powder using a mortar, and then 200 mg of the sample was weighed and evenly spread on a quartz boat. The sample was heated to 550°C at a heating rate of 10°C / min in an air atmosphere using a tube furnace and calcined for 9 h to obtain a mica-metal oxide composite nanomaterial named NiO / Mica.
[0057] Example 8 The precursor Ni / Mica obtained in step (2) of Example 1 was ground into powder using a mortar, and then 200 mg of the sample was weighed and evenly spread on a quartz boat. The sample was heated to 700°C at a heating rate of 10°C / min in an air atmosphere using a tube furnace, and calcined for 7 h to obtain a mica-metal oxide composite nanomaterial named NiO / Mica.
[0058] Example 9 2 mg of NiO / Mica, a mica-metal oxide composite nanomaterial prepared in Example 1, and 8 mg of carbon powder were dispersed in 1.5 mL of isopropanol, and 0.5 mL of Nafion solution (0.5 wt%) was added. Ultrasonication was performed for 30 min until a uniform catalyst slurry was formed. A 1×1 cm nickel-iron foam (5:5) was cut as a substrate, and the catalyst slurry was evenly brushed onto the surface of the nickel-iron foam substrate with a brush to form a working electrode for electrochemical performance testing. In a three-electrode system at room temperature, an electrochemical workstation was used, with a graphite rod and Ag / AgCl (4.0 M KCl) as the counter electrode and reference electrode, respectively, and the electrolyte was 1 M KOH.
[0059] Figure 4 The OER polarization curves of nickel-iron foam substrate, mica powder, precursor Ni / Mica, mica-metal oxide composite nanomaterial NiO / Mica and RuO2 are shown in Figure 2. Figure 4As can be seen from the figure, the activity of mica-metal oxide composite nanomaterial NiO / Mica is particularly outstanding, and only an overpotential of 270 mV is required to reach 10 mA cm -2 , which is higher than other materials (RuO2 is 295mV, Ni / Mica is 320mV, Mica is 321mV, and pure substrate is 355mV).
[0060] In order to gain a deeper understanding of the OER reaction pathway, the Tafel slopes of the OER polarization curves of various catalysts (foamed nickel iron substrate, mica powder, precursor Ni / Mica, mica-metal oxide composite nanomaterials NiO / Mica, and RuO2) are shown in Figure 2. Figure 5 As shown, from Figure 5 It can be clearly seen that compared with the substrate (260.9 mV dec -1 )、Mica(196.1 mV dec -1 )、Ni / Mica (176.2 mV dec -1 )、RuO2(102.3 mV dec -1 ), mica-metal oxide composite nanomaterial NiO / Mica (51.2 mV dec -1 ) electrode has a smaller Tafel slope. This shows that the NiO / Mica electrode has better intrinsic catalytic activity than other electrodes.
[0061] Electrochemical impedance spectroscopy was performed on the electrodes of various catalysts (foamed nickel iron substrate, mica powder, precursor Ni / Mica, mica-metal oxide composite nanomaterials NiO / Mica, and RuO2) to further study the catalytic kinetics. Figure 6 As shown in the figure, similar semicircular curves between different samples indicate similar electrochemical mechanisms and charge transfer characteristics. There is a linear correlation between the charge transfer resistance (Rct) and the semicircle diameter of the Nyquist curve. Through fitting, it is found that the NiO / Mica electrode has the smallest Rct value of 1.7 Ω, reflecting its faster charge transfer kinetics, which is consistent with the overpotential and Tafel slope mentioned above.
[0062] Example 10 In addition to excellent catalytic activity, stability is another important factor in measuring the quality of a catalyst. The stability test of NiO / Mica was carried out in an O2-saturated 1.0 M KOH solution, with a constant current density of 10 mAcm -2 To perform long cycle tests, such as Figure 7 After 111 hours of testing, the overpotential of the electrode prepared in Example 9 did not increase significantly, indicating its excellent stability.
[0063] Embodiment 11 In order to further understand the effect of Ni content on catalytic activity, only the mass of Ni was changed while keeping other conditions unchanged. The polarization curves of the NiO / Mica composite nanomaterials with different mica and nickel powder ratios prepared in Examples 1 to 6, and the working electrodes and substrates prepared according to the electrode preparation method in Example 9 are shown in FIG. Figure 8 It can be clearly seen that the sample in Example 1 has the best catalytic activity, which shows that the ratio of mica to nickel powder will affect the final catalytic activity effect.
Claims
1. A mica-metal oxide composite nanomaterial, characterized in that: The mica powder is used as a carrier and loaded with nickel oxide nanoparticles.
2. The mica-metal oxide composite nanomaterial according to claim 1, characterized in that: The particle size of mica powder is 5 to 8 μm; The nickel oxide nanoparticles are nanosheets, and the particle size of the nickel oxide nanosheets is 1 to 2 μm.
3. The method for preparing the mica-metal oxide composite nanomaterial according to claim 1 or 2, characterized in that: The following steps are involved: (1) ball-milling mica powder and nickel powder to obtain a precursor; (2) calcining the precursor in an oxygen atmosphere to obtain the mica-metal oxide composite nanomaterial.
4. The preparation method according to claim 3, characterized in that: In step (1), the mass ratio of the mica powder to the nickel powder is 3:2-6, preferably 3:
5.
5. The preparation method according to claim 3, characterized in that: In step (1), a ball milling aid needs to be added during the ball milling process, and the ball milling aid is ethanol.
6. The preparation method according to claim 3, characterized in that: In step (1), during the ball milling process, the ball-to-material ratio is (24-26):(1.8-2.2), preferably 25:2; Alternatively, in step (1), during the ball milling process, the ball milling speed is 350 to 500 r / min, preferably 400 r / min; and the ball milling time is 7 to 9 h, preferably 8 h.
7. The preparation method according to claim 3, characterized in that: In step (2), during the calcination process, the calcination temperature is 550-700° C., preferably 600° C.; the calcination time is 7-9 hours, preferably 8 hours; Preferably, during the calcination process, the heating rate is 8-12°C / min, preferably 10°C / min.
8. Use of the mica-metal oxide composite nanomaterial according to claim 1 or 2 as a catalyst.
9. The use according to claim 9, characterized in that The applications include: producing hydrogen by electrolyzing water.
10. A catalytic layer slurry for producing hydrogen by electrolysis of water, characterized in that: The invention comprises a binder, a conductive material and the mica-metal oxide composite nanomaterial according to claim 1 or 2.
Citation Information
Patent Citations
Two-dimensional NiO single crystal nanosheet as well as sodium chloride assisted chemical vapor deposition preparation method and application thereof
CN116815311A
Two-dimensional stepped nickel oxide nanosheet and preparation method thereof
CN118929791A
Tow dolly assembly
KR1020250162992A